What works in safety. The use and perceived effectiveness of 48 safety interventions. (June 2023) - van Kampen, Jakko; Lammers, Marre; Steijn, Wouter; Guldenmund, Frank; Groeneweg, Jop
Highlights: The effectiveness of safety interventions is often unclear in practice. Safety practitioners were surveyed on the intervention types that they use. The use and perceived effectiveness of these intervention types is shown. Abstract: In the Netherlands, approximately 2.300 workers have a serious reportable accident at work every year, of which around 60 are fatal (Inspectie SZW, 2020 ; Bellamy et al., 2014 ). Safety practitioners employ many methods to improve occupational safety for workers within their companies. Interventions might, for example, be aimed at improving companies' overall 'safety culture', at the introduction of a safety management system (e.g. Robson et al., 2007 ), or at improving the compliance of workers to specific safety rules (e.g. Peuscher and Groeneweg 2012; Bryden et al., 2016 ). However, the effectiveness of many of those interventions remains largely unclear (Dyreborg et al, 2015 ). The Dutch National Institute for Public Health and the Environment (RIVM) has started a project with the ultimate goal of developing a database filled with effective safety interventions. Developers can submit their interventions using a fixed protocol. To support this project, we developed a survey, which was sent to all members of the Dutch Society for Safety Science (NVVK). In the survey, we used a list of 48 predefined descriptions of common interventions. Respondents could indicate whether they made use of these common interventions and the extent to which they considered these effective. The survey thus provided an extensive overview of the use and perceived effectiveness of 48 specific safety interventions. In the future, these insights can support the development and testing of more effective safety interventions.